HAKEKAT PENDIDIK YANG SEBENARNYA - Amrullah Aziz Amrullah Aziz (Universitas Yudharta Pasuruan, 2017)
With emerging social issues in the community such as high crime rates, rampant cases, environmental damage and various other defects, often people considered that this is caused by the failure of education to deliver human resources more civilized, people who can keep themselves and their environment, Of these charges are not one hundred percent true, but nor completely wrong, because education has a strategic role of promoting human civilization. If the mind is accepted, then we need to do in-depth reflection on Which components that most influence on the success or failure of an educational process?